Cartography of urban floods in the Canal do Mangue basin – RJ: the new configuration post-macrodrainage works - Melos, Aline Riccioni de; Diniz, Tamiris Batista (National Journal of City Management, 2025)
Objective – To identify changes in the urban floodplain of the Canal do Mangue Basin (BCM) following the completion of macro-drainage works.Methodology – Questionnaires were administered to workers in the region previously affected, using data provided by the Municipality of Rio de Janeiro to guide the sampling process.Originality/Relevance – The study examines the impact of macro-drainage works completed in 2019 in the BCM, an area historically affected by urban floods. The research contributes to understanding the relationship between structural interventions and perceptions of changes in flood impacts.Results – Respondents reported improvements in flood characteristics, such as reduced water depth, frequency, and affected area extent. However, 73% still reported the occurrence of floods in front of their workplaces, particularly in lower-altitude areas.Theoretical/Methodological Contributions – The study reinforces the importance of combining empirical data, such as questionnaires, with geospatial and hydrological analysis to evaluate the impacts of macro-drainage interventions. This approach provides a nuanced understanding of urban flood dynamics and the effectiveness of infrastructure projects.Social and Environmental Contributions – The findings emphasize the need for additional interventions in low-elevation areas to address persistent flooding, highlighting the importance of inclusive urban planning. This can contribute to mitigating environmental risks and improving the quality of life for residents and workers in the CMB.
Keywords: Urban flooding; Risk perception; Canal do Mangue Basin